Externalizing and Internalizing Behaviors Among Adolescents with Learning Disabilities: Contribution of Adolescents' Attachment to Mothers and Negative Affect. - Al-Yagon, Michal (Journal of Child & Family Studies, 2015)
This study investigated incidence rates of internalizing and externalizing behaviors in the at-risk population of adolescents with learning disabilities (LD) and explored the shared and differing antecedents possibly underlying both maladaptive behavior types. The study aimed to examine a model of three personal vulnerability and protective factors in adolescents-negative affect, attachment to mothers, and sex-in predicting differences in externalizing and internalizing behaviors among adolescents with LD versus adolescents with typical development. Participants included 369 adolescents in Grades 10-11 (ages 15-17 years) from three demographically similar urban public high schools. Descriptive analyses yielded significant group differences on all three measures. Path analysis examined the contribution of this three-factor model for the adjustment of the LD and non-LD groups. A high fit emerged between the theoretical model and the empirical findings, supporting the study hypotheses concerning the role of all three personal factors in understanding differences in the two groups' internalizing and externalizing maladjustment. The present results also yielded partially different patterns of relations for the two groups, especially regarding adolescents' secure attachment to mothers and adolescents' sex as antecedents of maladaptive behavior. Results also indicated the mediating role of adolescents' negative affect in understanding how adolescents' sex and attachment to mothers were associated with their internalizing and externalizing behaviors. Discussion focused on understanding the differential value of these personal factors for understanding well-adjusted behavioral functioning in adolescents with versus without LD.